2007
DOI: 10.1002/glia.20583
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase of glial glutamate uptake via blockade of the protein kinase A pathway

Abstract: Glutamate is the main excitatory neurotransmitter in the vertebrate central nervous system. Removal of this transmitter from the synaptic cleft by glial and neuronal transporter systems plays an important role in terminating glutamatergic neurotransmission. The effects of different activators and blockers of PKA and PKC on glutamate uptake were studied in primary glial cells cultivated from the rat cortex using the patch-clamp recording technique and immunocytochemical methods. GF 109203X enhances glutamate-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…The size of GTCs reflects the amount of transported glutamate, which has been widely used as an effective tool to study the function of glial GTs. 14,36,50 We recently reported that mice with pSNL had lower amplitudes of GTCs. 14 After recording baseline GTCs in spinal slices taken from neuropathic GFP-GFAP mice, we perfused the AMPK activator (AICAR, concentration in the bath: 10 μM) into the recording chamber and recorded GTCs again.…”
Section: Resultsmentioning
confidence: 95%
“…The size of GTCs reflects the amount of transported glutamate, which has been widely used as an effective tool to study the function of glial GTs. 14,36,50 We recently reported that mice with pSNL had lower amplitudes of GTCs. 14 After recording baseline GTCs in spinal slices taken from neuropathic GFP-GFAP mice, we perfused the AMPK activator (AICAR, concentration in the bath: 10 μM) into the recording chamber and recorded GTCs again.…”
Section: Resultsmentioning
confidence: 95%
“…Fig. Accordingly, different studies have shown that the cAMP/protein kinase A transducing pathway can either enhance (Figiel et al, 2003;Gegelashvili et al, 1997), fail to affect (Danbolt, 2001;Gegelashvili et al, 1997) or decrease the expression or activity of GLT-I and GLAST (Adolph et al, 2007;Lim and Kim, 2003;Nishizaki et al, 2002;Rath et al, 2008) in astrocytic cultures. The presently observed severe decrease of GLT-I and GLAST activity and expression levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The increased EAAT activity in PrPKO versus WT astrocytes was accompanied by only a modest elevation in EAAT1 expression in PrPKO astrocytes, suggesting the alterations could be due to indirect mechanisms that effect surface localization and/or changes in intrinsic activity. L-Glutamate transporters are subject to interactions with modulating proteins (Jackson et al 2001) and to post-translational modifications that can result in altered transporter function (Adolph et al 2007; Duan et al 1999; Lin et al 2001; Munir et al 2000, Schlag et al 1998). The localization of PrP and EAATs to lipid rafts may provide an environment conducive to direct and/or indirect interactions between these proteins (Butchbach et al 2004; Naslavsky et al 1997).…”
Section: Discussionmentioning
confidence: 99%